Implementing Promotional Strategies And Improving Business Image At Sleman Industrial And Trade Offices On The Development Of MSME’s In Sleman District - Salsabila Adisa Putri; Drs. Dr. Albari M.Si (Cita konsultindo, 2024)
This research is research that examines promotion strategies and improving the image of MSME businesses implemented by the Sleman Regency Industry and Trade Service. This research uses a qualitative approach by involving the analysis unit in the process of collecting data and information through direct observation and interviews. This research is a form of the results of observations and interviews that the author conducted during the internship period. Some of the promotional strategies and improving the business image implemented by the Department of Industry and Trade are involving MSMEs in the Sleman area at the Craft Exhibition, building a jadah tempe education tourism center, and holding a virtual MSME business expo or exhibition. The findings from this research are that the promotion strategy and image improvement of MSMEs has been successfully implemented effectively as shown by the increase in the number of MSMEs per year, increasing sales, and forming a good brand image in the minds of customers.